Modifiable risk factors associated with disposal of unused prescription drugs by parents of adolescents - Egan, Kathleen L. (My University, 2020)
The safe disposal of unused medications is one primary prevention strategy to reduce nonmedical prescription drug use among adolescents. We sought to identify modifiable risk factors associated with disposal of unused prescription drugs by parents of adolescents residing in ten south central Kentucky counties with disposal programs. In the fall of 2017, 4148 parents of adolescents participated in an anonymous, paper-based survey. We conducted generalized logit mixed models adjusted for within-school clustering to assess the relationship between disposal behaviors and modifiable risk factors while controlling for respondents’ sociodemographic characteristics. The analytic sample consisted of parents in households in which someone had been prescribed an opioid medication within the past 12 months (N = 627). Our findings indicated that almost 42% of parents reported disposing of unused prescription medication within the past 12 months, and the majority disposed of medications at home rather than using a disposal program. Parents who perceived that any, compared to none, of their child’s close friends engaged in nonmedical prescription opioid use had higher odds of reporting use of a disposal program. Parents who were aware of disposal programs, compared to those who were not aware, had greater odds of using them, rather than not disposing at all or disposing unused prescription medications at home. Compared to parents who perceived prescription drugs to be hard for adolescents to obtain for nonmedical use, parents who believed that prescription drugs were easily accessible to adolescents for nonmedical use had lower odds of using disposal programs than disposing of medications at home. Collectively, our findings suggest that enhancing awareness of disposal programs, while addressing parents’ perceptions of their children’s peers’ use of nonmedical prescription opioids, should be considered to facilitate the disposal of unused medications and optimize current public health prevention efforts related to adolescent nonmedical use of these drugs.
Keywords: Prescription drug; Adolescent; Opioid; Parent; Prevention